Curriculum Reform in Islamic Religious Education: A Competency-Based Approach in Indonesian Madrasah Ibtidaiyah - Adib, Muhammad; Pahrudin, Agus; Jatmiko, Agus; Koderi, Koderi (Bidayatuna, 2024)
The Competency-Based Curriculum for Islamic Religious Education in Madrasah Ibtidaiyah aims to enhance students' cognitive, affective, and psychomotor skills in alignment with Islamic values. This study investigates the implementation of the Competency-Based Curriculum in Islamic Religious Education at Madrasah Ibtidaiyah and identifies challenges encountered during its application. Using qualitative methods, data were collected through interviews, observations, and document analysis, then analyzed descriptively to explore the relationship between the objectives of the Competency-Based Curriculum and its implementation in the field. The findings reveal that the Competency-Based Curriculum fosters a deeper understanding of Islamic teachings while aligning education with contemporary demands. However, challenges such as insufficient resources, limited teacher training, and resistance to curriculum changes hinder its effectiveness. The study concludes that successfully implementing the Competency-Based Curriculum in Islamic Religious Education at Madrasah Ibtidaiyah requires adequate teacher preparation, improved learning facilities, and active stakeholder participation. Additionally, the curriculum must adapt to student's needs and be supported by robust policies for sustainable application.